Paraganglioma of nose: a common tumor, rare site - Khandekar, Sanjay; Chide, Pratik; Lodha, Nilima; Mahadani, Jayawant; Hingway, Snehalata; Yedshikar, Vikas; Pagrut, Keshav; Khandekar, Hitendra; Kunghadkar, Vijay (International Journal of Research in Medical Sciences, 2017)
Paragangliomas are neuroendocrine tumors, arising from paraganglionic tissue. They most commonly originates in adrenal gland and are known as pheochromocytoma. However 5-10% of these tumor are extra-adrenal and may appears in neck and pelvic region along sympathetic nervous system.1 In the head and neck, the most common sites of origin of this neoplasm are the carotid body, the jugular bulb and the vagal body. Paragangliomas arising from nose are very rare. We here report a rare case of paragangiloma of nose diagnosed on histopathology.